Characterization of phase transformations during graded thermo- mechanical treatment of steel 22MnB5 by means of optical methods - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Materials Data for Smart Forming Technologies)

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)

Interdiffusion in aluminum-steel clad strip - Krivská, Barbora; Šlapáková, Michaela; Kihoulou, Martin; Králík, Rostislav; Bajtošová, Lucia; Cieslar, Miroslav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Proc. 20th Conference of Czech and Slovak Physicists)

Aluminum-steel clad material prepared by twin-roll casting - KŘIVSKÁ, Barbora; ŠLAPÁKOVÁ, Michaela; Grydin, Olexandr; CIESLAR, Miroslav (METAL 2020 Conference Proeedings)

Deformation of expanded steel mesh inlay inside aluminum matrix during the roll bonding - Frolov, Yaroslav; Haranich, Yurii; Bobukh, Olexandr; Remez, Oleg; Voswinkel, Dietrich; Grydin, Olexandr (Journal of Manufacturing Processes)

Cold rolling of pre-profiled strips from aluminum alloy EN AW-1050 - Bondarenko, Serhii; Grydin, Olexandr; Frolov, Yaroslav; Kuzmina, Olga; Bobukh, Olexandr (Modern Problems of Metallurgy – Scientific Bulletin)

Phase Transformation Characterization by Means of High Temperature Digital Image Correlation for Graded Thermo-Mechanical Processing of Sheet Parts - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (The Minerals, Metals & Materials Series)

Time efficient laser modification of steel surfaces for advanced bonding in hybrid materials - Voswinkel, D.; Kloidt, D.; Grydin, O.; Schaper, M. (Production Engineering)
Abstract Laser surface treatment of metals is one option to improve their properties for adhesive bonding. In this paper, a pulsed YVO4 Laser source with a wavelength of 1064 nm and a maximum power of 25 W was utilized to increase the surface area of the steel HCT490X in order to improve its bonding properties with a carbon fibre reinforced polymer (CFRP). Investigated was the influence of the scanning speed of the laser source on the bonding properties. For this purpose, the steel surfaces were ablated at a scanning speed between 1500 and 4500 mm/s. Afterwards the components were bonded with the adhesive HexBond™ 677. After lap shear tests were carried out on the specimen, the surfaces were inspected using scanning electron microscopy (SEM). The experiments revealed that the bonding quality can be improved with a high scanning speed, even when the surface is not completely ablated.

Influence of Nozzle Shape on Near-Surface Segregation Formation During Twin-Roll Casting of Aluminum Strips - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Light Metals 2020)

Kurzzeitaustenitisierung höchstfester Stähle – eine zeiteffiziente Methode zur Fertigung sicherheitsrelevanter Bauteile mit verbesserten Eigenschaften - Andreiev, Anatolii

Development of SLM Ni-based Superalloys and Investigation of Corrosion Behavior in Chloride-containing Environments - Wooldridge, Madison

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christoph; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Condensed Matter Physics

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization of Phase Transformations During Graded Thermo-Mechanical Processing of Press-Hardening Sheet Steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract Safety-relevant components in automobiles require materials that combine high strength with sufficient residual ductility and high-energy absorption. A graded thermo-mechanical treatment of the press-hardening steel 22MnB5 with graded microstructure can provide a material with such properties. Different austenitization temperatures, cooling and forming conditions within a sheet part lead to the development of microstructures with mixed phase compositions. To determine the resulting phase contents in such graded processed parts, a large number of dilatometric tests are usually required. With a non-contact characterization method, it is possible to detect local phase transformations on an inhomogeneously treated flat steel specimen. For press-hardening steel after heat treatment and thermo-mechanical processing, correlations between austenitization temperature, hot deformation strain, microstructure, and hardness are established.

New Twin-Roll Cast Al-Li Based Alloys for High-Strength Applications - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko; Belejová, Sára; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Cieslar, Miroslav (Metals)
Al-Li based alloys are attractive materials for the aerospace industry. The twin-roll casting of such materials could provide properties not achievable by conventional direct-chill casting and downstream processing methods due to significantly higher solidification rates. An Al-Li-Cu-Mg-Zr alloy was twin-roll cast with the same alloy containing a small addition of Sc. The microstructure of as-cast materials and the influence of Sc on the behavior of the alloy at elevated temperatures were studied by means of light and electron microscopy and by resistivity measurements. A fine-grained structure was formed during twin-roll casting, but several surface and internal defects were found on the strips, which should be suppressed by a further adjustment of the casting conditions. The addition of Sc had a positive effect on grain size uniformity and microstructure stabilization at elevated temperatures, as shown by the precipitation of a fine dispersion of coherent Sc- and Zr-containing precipitates.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Strain parameters at hot rolling of aluminum strips reinforced with steel netting - Stolbchenko, Mykhailo; Makeieva, Hanna; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Journal of Sandwich Structures & Materials)
This experiment studied the strain parameters of rolling an aluminum matrix when wire netting is inserted between aluminum layers. During the experiment, two types of stainless steel fabric netting oriented parallel and diagonal to the rolling axis were placed between two aluminum strips and rolled. Multiple rolling processes were performed in which the temperature and pressure on the material were varied to produce bonding of matrix layers. During the study, the following main investigations were made: strain on areas of longitudinal and transverse cross sections of the composite was measured; stretching and ovalization of net wiring and changes in the net cell angles were determined; mechanical properties of composites along the rolling direction were tested. The main contradiction resulting from this experiment was as follows: the contact pressure required for the bonding of aluminum layers produces extreme tensile strain on the inserted net wires, reducing the mechanical properties of the reinforcing net and thus reducing properties of the entire composite. Optimal results in the longitudinal tension tests were achieved by using strips with diagonally oriented net-reinforcement.

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, T.; Teng, Z.J.; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

The mechanical properties of rolled wire-reinforced aluminum composites at different strain values - Stolbchenko, Mykhailo; Frolov, Yaroslav; Makeieva, Hanna; Grydin, Olexandr; Tershakovec, Michael A.; Schaper, Mirko (Mechanics of Advanced Materials and Structures)

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christopher; Liß, Jan; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, W.; Hagen, L.; Schaak, C.; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, M. E.; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, Tobias; Teng, Zhenjie; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Influence of Microstructure in Near‐Surface Areas of Feedstocks on the Bond Strength of Roll Bonded Aluminum Clads - Grydin, Olexandr; Matzelt, Manuel; Andreiev, Anatolii; Frolov, Yaroslav; Schaper, Mirko (Advanced Engineering Materials)

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslaw; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Alloy Design for Biomedical Applications in Additive Manufacturing - Hoyer, Kay-Peter; Schaper, Mirko (TMS 2019 148th Annual Meeting & Exhibition Supplemental Proceedings)

Surface Inoculation of Aluminium Powders for Additive Manufacturing Guided by Differential Fast Scanning Calorimetry - Tasche, Lennart; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Grundmeier, Guido; Schaper, Mirko; Keßler, Olaf (TMS 2019 148th Annual Meeting & Exhibition Supplemental Proceedings)

Einfluss von Eigenspannungen und Oberflächenrauheit additiv gefertigter Komponenten aus 316L auf die Beschichtbarkeit und Ermüdungsfestigkeit,

Adhesion of HVOF sprayed WC-Co coatings on additively processed 316L

Mikrostrukturelle und mechanische Eigenschaften der im Laserschmelzverfahren verarbeiteten Inconel 718 Nickelbasis-Superlegierung - Aydinöz, Mehmet Esat
Im Rahmen dieser Arbeit wurden die mikrostrukturelle Entwicklung und die daraus resultierenden mechanischen Eigenschaften der im SLM® Verfahren (Selective Laser Melting) verarbeiteten Nickelbasis-Superlegierung Inconel 718 untersucht. Anschließend wurde der Einfluss des HIP-Prozesses (Heißisostatisches Pressen) auf die Porosität, die Mikrostruktur und die mechanischen Eigenschaften analysiert. Da der HIP-Prozess oberflächennahe Poren nicht schließen kann, wurden ausgewählte Proben durch das Arc-PVD-Verfahren (Physical Vapor Deposition) mit einer Ni-20Cr Beschichtung gekapselt. Da die typischen Zellstrukturen zusammen mit den γ´´- Ausscheidungen nach dem Lösungsglühen mit anschließender Ausscheidungshärtung auftreten, konnte die höchste Streckgrenze (Rp0,2) unter quasistatischer Belastung bei Raumtemperatur (RT) sowie bei 650 °C ermittelt werden. Unter zyklischer Belastung zeigen die beschichteten und heißisostatisch gepressten Proben die geringste Ermüdungsfestigkeit bei RT, sowohl vor als auch nach der Ausscheidungshärtung. Im lösungsgeglühten und anschließend ausscheidungsgehärteten Zustand weist das Material die höchste Lebensdauer, insbesondere bei einer niedrigen Dehnungsamplitude (Δε/2 = ±0,35 %), bei 650 °C auf.
Keywords: Additive Fertigung; Laserschmelzverfahren; Nickelbasis-Superlegierung; Inconel 718; Mikrostruktur; mechanische Eigenschaften; Heißisostatisches Pressen; Beschichtung

Intrinsically lubricated tool inserts for deep drawing applications generated by selective laser melting - Bader, Fabian; Hengsbach, Florian; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)
Abstract. Within the scope of this study, an intrinsically lubricated deep drawing die fabricated via laser beam melting (LBM) is investigated. In contrast to the common objective of generating highly dense LBM components, this work endeavors to achieve intended micro-scale porosity. By utilizing permeable structures, in-process closed-loop control of lubrication during the forming operations is feasible. Based on a modified AM scan strategy, the required filigree, porous structures can be generated. Thus, in the present work three permeable specimens are additively generated from the maraging steel 1.2709. The cylindrical specimens are then analyzed via light microscopy (LM), microcomputer tomography (microCT), and with regard to the oil throughput rate. Subsequently, an intrinsically lubricated, AM deep drawing tool die is manufactured and experimentally tested. The findings reveal interesting results for deep drawn specimens with AM deep drawing dies.

Laserinduzierte Nanostrukturierung intrinsisch gefertigter Hybridstrukturen – Oberflächenmorphologie, Verbindungs- und Korrosionseigenschaften - Zinn, Carolin

Surface Inoculation of Aluminium Powders for Additive Manufacturing Guided by Differential Fast Scanning Calorimetry - Tasche, Lennart; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Grundmeier, Guido; Schaper, Mirko; Keßler, Olaf (The Minerals, Metals & Materials Series)

Flexible Hot Rolling of Extruded Shapes of Aluminum Alloy EN AW-6082 - Grydin, Olexandr; Sotirov, Nikolay; Samsonenko, Andrii; Biba, Nikolay; Andreiev, Anatolii; Stolbchenko, Mykhailo; Behr, Teresa; Frolov, Iaroslav; Schaper, Mirko (Materials Science Forum)
One of the strategies employed to lower weight and to decrease material consumption is reducing part thickness itself. Thus, functionally graded materials in which structural reinforcement is adjusted locally, are of great interest. With regard to conventional industrial processes, such as extrusion or flexible cold rolling, thickness variations can only be achieved either longitudinally or through the cross-section of the semi-finished products. Hence, a combined thickness variation (along both axes) is difficult to generate solely by extrusion or rolling. A simultaneous thickness variation in both directions, however, would enable further weight savings in structural components such as car body parts. In this study, a promising approach with extruded shapes, serving as a billet for a flexible hot rolling process, is elaborated upon. By employing the described process modification, shapes with simultaneous thickness variations in longitudinal as well as in transverse direction are feasible. Initial numerical analysis reveals the weight-saving potential of using these semi-finished products for structural parts in a car body. A demonstration of the production process for the semi-finished parts and the occurring challenges are discussed. To verify and adjust the new technology, a numerical model of the flexible hot rolling process has been created based on the finite element software QForm VX. This model is also employed for tool design optimization to produce semi-finished components with the required geometrical quality. Finally, the results of hot rolling experiments conducted using the adjusted roll design are presented.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; General Chemistry; Bioengineering

Short austenitization treatment with subsequent press hardening: Correlation between process parameters, microstructure and mechanical properties - Grydin, Olexandr; Andreiev, Anatolii; Holzweißig, Martin Joachim; Rüsing, Christian Johannes; Duschik, Kristina; Frolov, Yaroslav; Schaper, Mirko (Materials Science and Engineering: A)

Relationships between Microstructural and Mechanical Performance on Example of an Air‐Hardening Steel - Grydin, Olexandr; Andreiev, Anatolii; Zogaj, Mergim; Frolov, Yaroslav; Schaper, Mirko (Advanced Engineering Materials)

Additive Manufacturing of a Soft Magnetic Rotor Active Part and Shaft for a Permanent Magnet Synchronous Machine - Urbanek, Stefan; Ponick, Bernd; Taube, Alexander; Hoyer, Kay-Peter; Schaper, Mirko; Lammers, Stefan; Lieneke, Tobias; Zimmer, Detmar (2018 IEEE Transportation Electrification Conference and Expo (ITEC))

Einfluss unterschiedlicher Pulvereigenschaften beim selektiven Laserstrahlschmelzen von TiAl6V4 auf die Werkstoffeigenschaften

Metallische Legierungssysteme für die additive Fertigung belastungsangepasster Implantate

Inline additively manufactured functionally graded multi-materials: microstructural and mechanical characterization of 316L parts with H13 layers - Hengsbach, Florian; Koppa, Peter; Holzweissig, Martin Joachim; Aydinöz, Mehmet Esat; Taube, Alexander; Hoyer, Kay-Peter; Starykov, Oleksiy; Tonn, Babette; Niendorf, Thomas; Tröster, Thomas; Schaper, Mirko (Progress in Additive Manufacturing)

Inline additively manufactured functionally graded multi-materials: microstructural and mechanical characterization of 316L parts with H13 layers - Hengsbach, Florian; Koppa, Peter; Holzweissig, Martin Joachim; Aydinöz, Mehmet Esat; Taube, Alexander; Hoyer, Kay-Peter; Starykov, Oleksiy; Tonn, Babette; Niendorf, Thomas; Tröster, Thomas; Schaper, Mirko (Progress in Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering

Anodizing of electrolytically galvanized steel surfaces for improved interface properties in fiber metal laminates - Engelkemeier, Katja; Mücke, Christian; Hoyer, Kay-Peter; Schaper, Mirko (Advanced Composites and Hybrid Materials)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Ceramics and Composites

Influence of sp3/sp2-carbon ratio of vertically standing carbon nanostructures produced by pulsed laser-treatment on PAN-based carbon fibers - Engelkemeier, Katja; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Anodizing of electrolytically galvanized steel surfaces for improved interface properties in fiber metal laminates - Engelkemeier, Katja; Mücke, Christian; Hoyer, Kay-Peter; Schaper, Mirko (Advanced Composites and Hybrid Materials)